Correlation between quadriceps activation and proprioception in patients with knee osteoarthritis - Yang, Meiping; Ge, Zhilin; Gao, Zibo; Zeng, Xiaolong; Li, Yongjin; Lin, Dingkun; Hou, Yu (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectiveTo investigate the correlation between the activation status of quadriceps muscle and the proprioceptive accuracy in patients with knee osteoarthritis (KOA).MethodsWe included 43 outpatients diagnosed with KOA and 45 health subjects from October 2024 to May 2025. The correlation between the absolute error in knee Joint Position Reproduction (JPR) and the root mean square (RMS) and median frequency (MDF) of quadriceps surface electromyography during walking and stair climbing was analyzed.ResultsThe JPR of 45° in KOA patient is significantly higher than health subjects. There was no significant difference in 30° and 60° JRP between the two groups. While walking, there is no significant difference of the sEMG data in two group. While going up stair, the RMS of LVM and RVM in KOA group had increased activation compared with the health subjects. In KOA group, while going up stair, the JPR absolute error angle of 30° was negatively correlated with the MDF of RVL, the JPR absolute error angle of 45° was positively correlated with the RMS of RVM, and the JPR absolute error angle of 60° was positively correlated with RMS of LVM and RVM. There are no significantly correlation in JPR absolute error angle and the surface electromyography of the quadriceps muscle while walking and in health control group. Partial correlation analysis was performed on the aforementioned correlated indicators with gender included as a control variable, and the results indicated that in women group, the JPR absolute error angle of 60° was positively correlated with RMS of LVM and RVM. In KOA group, the RMS of LVL, RVL and RVM in walking was positively correlated with the RMS of LVL, RVL and RVM in going up and down stair, and the MDF of LVL, RVL and RVM in walking was positively correlated with the MDF of LVL, RVL and RVM in going up and down stair. In health control group, the MDF of LVL, RVL and RVM in walking was positively correlated with the MDF of LVL, RVL and RVM in going up and down stair.ConclusionThis study indicated that during stair climb, KOA patients display a unique pattern of elevated RMS of the VM. Notable relationships were identified between the absolute error angles of JPR and sEMG parameters of VM. The pronounced positive correlations in muscle activation patterns between walking and stair upward and downward activities indicate a fixed, task-invariant neuromuscular approach in KOA patients, possibly resulting from compromised sensorimotor integration due to proprioceptive impairments. These findings offer new insights into the pathogenesis of KOA from a neuromuscular-sensory viewpoint, emphasizing the need for future rehabilitation therapies to concurrently target proprioceptive accuracy and the enhancement of muscle activation patterns.